An overview of methods to qualitatively and quantitatively characterize the structure of polymer-coated cardboards: Advantages and limitations - Allison Vercasson; Sébastien Gaucel; Valérie Guillard; Hélène Angellier-Coussy (Materials & Design)
Polymer-coated cardboards are increasingly replacing conventional plastics for packaging applications. Understanding and quantifying the complex structure of these multilayered materials is essential for assessing the coating quality and predicting the performance; however, it remains challenging. This review aims to gather the existing knowledge and advances in experimental techniques and methods developed to characterize the structure of polymer-coated cardboards by systematically highlighting their advantages and limitations. The first part presents the evaluation of the surface coating quality (i.e., its homogeneity and the presence or absence of defects), starting from the detection of surface defects in the coating layer to their visualization and quantification with techniques such as SEM and X-ray tomography. The second part focuses on the evaluation of the thickness of each layer making up the material, which is necessary for predictive modeling and the production of just-necessary food packaging, ranging from visualization approaches to methods that rely on physical measurements. The third part reviews methods for characterizing the cardboard porosity, which is a key property for further modeling approaches as the impregnation of the polymer depends on it.